The 2nd International Cell Death Research Congress 2018
DOI: 10.3390/proceedings2251566
|View full text |Cite
|
Sign up to set email alerts
|

Apoptotic Effects of Opuntia ficus indica L. Seed Oils on Colon Adenocarcinoma Cell Lines

Abstract: Opuntia ficus indica L. fruit (cactus pear) seed oil is used in traditional and complementary therapies for its numerous health benefits. The aim of this study was to analyse of the fatty acid content and apoptotic induction effects of spiny and thornless Opuntia ficus indica L. seed (CPS) oils. Spiny and thornless Opuntia ficus indica L. seed oils obtained by supercritical CO2 extraction method and analyzed by GC-MS. Different concentrations of almond oils were incubated for 24 h and 48 h with Colo-320 and Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 7 publications
(7 reference statements)
1
8
0
Order By: Relevance
“…A previous study also supports our results, they have reported apoptotic activity of extracts of opuntia ficus indica L against cancer cell lines using TUNEL assay. The plant belongs to the same family from which our test compound Opuntiol has been extracted and also possess anti-inflammatory activity (Becer et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study also supports our results, they have reported apoptotic activity of extracts of opuntia ficus indica L against cancer cell lines using TUNEL assay. The plant belongs to the same family from which our test compound Opuntiol has been extracted and also possess anti-inflammatory activity (Becer et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In another previous study prickly pear cactus seed oil was studied for its anti-cancer activity against colon cancer cell lines. As a result, cell viability has been observed significantly in some colon cancer cell lines (Becer et al 2018). In addition, the anti-cancer activity of indicaxanthin, which is known to be highly present in the fruits of O. ficus-indica, on melanoma cancer was investigated by in vivo and in vitro methods and very successful results were obtained (Allegra et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, fatty acid content also differed among wild and cultivated prickly pear grown in Cyprus [ 16 ], and the main compounds of wild oil were linoleic acid that accounted for 55.9%, oleic acid 17.6%, palmitic acid 12.4% and elaidic acid 4%, while cultivated oil contains linoleic acid of 60.1%, oleic acid 15.6%, palmitic acid 12.3% and elaidic acid 4.1%. Among the two typologies, cultivated contained more linoleic acid compared to the wild species.…”
Section: Chemical Characterization Of the Prickly Pear Seed Oilmentioning
confidence: 99%
“…(The authors also found the inhibition effect of cell growth in cells that were treated with PPSO to be parallel with an increase of ROS in the cells, suggesting a ROS-induced cell death likely due to the pro-oxidant effects of the extracts). However, the PPSO was effective at inhibiting Colo-320 and Colo-741 growth [ 16 ], where the apoptotic effects of spiny (wild) and thornless (cultivated) forms of Opuntia ficus indica L. grown in Cyprus were studied against Colo-320 and Colo-741 cells for 48 h. Cell growth and cytotoxicity were measured by MTT assays. The spiny and thornless PPSO (1:16 dilution) were found to be active against the inhibition of Colo-320 and Colo-741 cell growth for 48 h. The author suggested that the inhibitory effect of thornless PPSO is due to the high linoleic acid content, which is a known compound with an anticancer effect in cancer cells.…”
Section: Potential Health Benefits Of Prickly Pear Seeds Oilmentioning
confidence: 99%
See 1 more Smart Citation